PEMBUATAN GREEN INFRASTRUCTURE PDAM DESA DAN JARINGAN PIPA PENYALURAN AIR BERSIH DENGAN POMPA HIDRAM DI DESA BANTERAN KECAMATAN SUMBANG KABUPATEN BANYUMAS - Imanda, Putri Rieski; Nurrohman, Reza Kusuma; Masyhuri, Hasby Syarifuddin; Srimurni, Rafika Ratik; Ila’la, Afana Riesma; Ardiansyah, Ardiansyah (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Banteran village especially Danalaya halmet is located at the foot of Slamet mountain with the contours of the hilly villages so that the location of residential areas is higher than in the river around the village, as well as their water source. With these conditions, the pump installation built hidram that is the water pump hydropower that serves to pump the water to burst higher than the waterfall, so the clean water needs at Danalaya halmet can be met. Network hidram pump clean water from the new turns up at one point and has not spread to the rest of the villagers so that not all villagers can enjoy it and it is a problem that must be solved. Given the problems we plan to help villagers Danalaya in the water distribution network by making clean water and we want to raise the water higher so water can be channeled to the whole house of the villagers. We use additional solar-powered pump (Green Infrastructure), so that the location of the water tank and the higher availability of clean water dealer network along with the water meter, it is expected the entire village can enjoy the clean water has been channeled later. PDAM of village also formed to regulate water usage recorded by the water meter so that the operational costs of water usage can be adjusted by the amount of water consumption per home residents.Â Keywords : water, solar power, hydram pump, water hammer,Banteran,green infrastucture.